2018
DOI: 10.3390/nu10040481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blue Mussel (Mytilus edulis) Intake on Disease Activity in Female Patients with Rheumatoid Arthritis: The MIRA Randomized Cross-Over Dietary Intervention

Abstract: Rheumatoid Arthritis (RA) is a chronic inflammatory disease. This study evaluates the effect of blue mussel intake on disease activity and quality of life in women with RA. Thirty-nine women with established RA and a disease activity score 28 (DAS28) >3.0 were recruited to a randomized 2 × 11-week cross-over dietary intervention. The participants continued with their medication and habitual diet and exchanged one cooked meal a day, five days a week, with a meal including 75 g blue mussels or 75 g meat. Diets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Two RCT studies investigated the effects of food items on disease activity—one parallel trial studying the intake of cranberry juice [ 23 ] and one crossover trial studying the intake of blue mussels [ 24 ]. The studies included 39 and 41 participants, all female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two RCT studies investigated the effects of food items on disease activity—one parallel trial studying the intake of cranberry juice [ 23 ] and one crossover trial studying the intake of blue mussels [ 24 ]. The studies included 39 and 41 participants, all female.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included 39 and 41 participants, all female. Lindqvist et al compared the effect of one daily ready-to-eat meal (5 days/week) for 11 weeks, supplemented with either 75 g blue mussels or chicken/red meat [ 24 ]. Thimoteo et al compared a usual diet supplemented with 500 mL/day low calorie cranberry juice to a usual diet, for 3 months [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participating patients and experimental design were described in detail in our previous publication [8]. Briefly, 39 women (25-65 years of age) with established RA and DAS28 >3.0 were allocated to start with either the blue mussel or control diet in a randomized, singleblinded cross-over intervention.…”
Section: Subjects and Experimental Designmentioning
confidence: 99%
“…RA affects 0.5-1% of the population globally, predominantly women [7]. We have previously shown, in the randomized cross-over trial Mussels, Inflammation and RA (MIRA), that disease activity, fatigue, pain and general health in RA is improved by a dietary intervention with blue mussels [8]. Briefly, intake of blue mussels led to a significant reduction in disease activity score 28 (DAS28)-C-reactive protein (CRP), with a trend towards significance for reduced CRP and reduced white blood cell count.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that fatty acid from M. edulis possess anti-inflammatory activity in arthritis rats without adverse side effects [18]. The most recent study, reported that supplementation of M. edulis can reduced the pain and fatigue in patient with rheumatoid arthritis (RA) [19].However, effects of Mytilus edulis water extract on male reduction dysfunction in obese rats haven't been reported. Based on this condition, this study aims to investigate the effects of Mytilus edulis water extract (MWE) on male reproduction dysfunction in high-fat diet (HFD)-induced obese rats.…”
Section: Introductionmentioning
confidence: 99%